Great Expectations: Hindu Revival Movements in Java - Reuter, Thomas (The Australian journal of anthropology, 2001)
Based on preliminary ethnographic research in five Javanese communities with major Hindu temples, I explore the political history and social dynamics of Hindu revivalism. I reject formalist approaches to the study of religion, including the notion of ‘syncretism’ and instead, treat the Hindu revival movements as an illustration of how social agents employ religious or secular concepts and values in their strategic responses to the particular challenges and crises they may face in a specific cultural, social, political and historical setting. Expectations of a great crisis at the dawn of a new golden age among followers of the Javanese Hindu revival movement are an expression of utopian prophesies and political hopes more widely shared among contemporary Indonesians. These expectations are set to shape the prospects of Indonesia's fledgling democracy. The paper reflects on the historical conditions under which these and similar utopian expectations and associated social movements may either incite violent conflict or serve a positive role in the creation or maintenance of a fair society.